A POPULATION STUDY OF BLUE PILCHARDS (Sardinops neopilchardus) IN SOUTH AUSTRALIA WATER USING ALLOZYME ELECTROPHORESIS - Winda Mercedes Mingkid (JOURNAL OF COASTAL DEVELOPMENT, 2005)
The biology and population analysis of Australian pilchards (Sardinops eopilchardus) was reviewedand studied. The Australian pilchards stock was depleted in South Australia whereas in other statesare under-exploited. The population study was done using protein analysis. Six enzymes (PEPB,AH, PGM, EST, MPI and AAT), which showed polymorphism, were scored and used in thepopulation study. For future studies, frozen procedure techniques need to be improved and numberof samples collected need to be extended.